A semantic analysis of key management protocols for wireless sensor networks - Macedonio, Damiano; Merro, Massimo (Science of computer programming, 2014)
Gorrieri and Martinelli’s timed Generalized Non-Deducibility on Compositions (tGNDC) schema is a well-known general framework for the formal verification of security protocols in a concurrent scenario. We generalise the tGNDC schema to verify wireless network security protocols. Our generalisation relies on a simple timed broadcasting process calculus whose operational semantics is given in terms of a labelled transition system which is used to derive a standard simulation theory. We apply our tGNDC framework to perform a security analysis of three well-known key management protocols for wireless sensor networks: μTESLA, LEAP+ and LiSP. ► We generalise Gorrieri and Martinelli’s tGNDC security framework. ► Our generalisation relies on a simple timed broadcasting process calculus. ► Our generalisation relies on a standard simulation theory. ► We apply our generalisation to verify real-world wireless networks key management protocols.